Sediment Provenance of the Nansha Trough Since 40 ka B.P. in the South China Sea: Evidence From δ13Corg, TOC and Pollen Composition - Thilakanayaka, Vidusanka; Chuanxiu, Luo; Xiang, Rong; Devendra, Dhanushka; Dasanayaka, S. A. H. K.; Jiang, Weiming; Rahman, Ananna; Kumar, Sazal; Ariful, G. M. (Frontiers in Earth Science, 2019)
Geochemical proxies in organic matter (OM) are considered to be reliable proxies for deciphering types of paleo-vegetation (C3 plants and C4 plants) and their abundance. The contributions of total organic carbon (TOC), stable carbon isotopes (δ13Corg), total nitrogen (TN) and organic carbon to total nitrogen ratios (C/N) were obtained from a gravity core NS07-25 (6°39.945′ N, 113°32.936′ E, water depth 2006 m), extracted from the southern South China Sea (SCS). These data were used to reconstruct the climate changes of the Nansha Trough since 40ka B.P. by comparing them with pollen data from the same core, and this comparison provides better sediment provenance details in the study area. During the periods between 37ka to 27ka, and from 12.5ka to modern day, the majority of terrestrial sediment received from Borneo, and some climatic events have been governed by aeolian fluxes from mid-latitude areas (mainland China). These periods were relatively humid, compared to 27ka to 12.5ka, where the majority of terrestrial sediment came from the Sunda Shelf through riverine pathways. This study serves as the first study to correlate deep oceanic pollen and geochemical proxies in order to identify the weaken terrestrial OM signals in the deep ocean.